2022
DOI: 10.1101/2022.05.24.493213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The substrate scopes of enzymes: a general prediction model based on machine and deep learning

Abstract: For a comprehensive understanding of metabolism, it is necessary to know all potential substrates for each enzyme encoded in an organism's genome. However, for most proteins annotated as enzymes, it is unknown which primary and/or secondary reactions they catalyze, as experimental characterizations are time-consuming and costly. Machine learning predictions could provide an efficient alternative, but are hampered by a lack of information regarding enzyme non-substrates, as available training data comprises mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…In our study on predicting the substrate scope of enzymes 30 , we found that prediction performance depends strongly on the sequence similarity between a target enzyme and enzymes in the training set, consistent with the widely held belief that enzymes are more likely to be functionally similar if they have more similar sequences [34]. We hence examined the performance of TurNuP for enzyme sets that differed in their maximal similarity to proteins in the training set.…”
Section: Turnup Provides Meaningful Predictions Even If No Close Homo...supporting
confidence: 67%
See 2 more Smart Citations
“…In our study on predicting the substrate scope of enzymes 30 , we found that prediction performance depends strongly on the sequence similarity between a target enzyme and enzymes in the training set, consistent with the widely held belief that enzymes are more likely to be functionally similar if they have more similar sequences [34]. We hence examined the performance of TurNuP for enzyme sets that differed in their maximal similarity to proteins in the training set.…”
Section: Turnup Provides Meaningful Predictions Even If No Close Homo...supporting
confidence: 67%
“…In a previous project 30 , we created a fine-tuned and task-specific version of the ESM-1b model that led to improved predictions for the substrate scope of enzymes, a problem for which abundant training data exists. Such comprehensive data is required to re-train the ESM-1b model, but is not available for k cat , and we were thus unable to create a version specific to the task of predicting k cat .…”
Section: Numerical Enzyme Representations Alone Lead To Reasonable K ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The second example is a project that uses deep learning to predict the substrate scope of enzymes [10]. Our initial idea was to simply modify a prediction pipeline that we had developed previously for the Michaelis constants of enzymes, K m [11].…”
Section: Science Is a Meta-puzzlementioning
confidence: 99%
“…We indeed found a solution: we added another "layer" to an existing numerical representation [12] of amino acid sequences. Training this model on our enzyme data, we could teach it to produce output that was more informative for our predictions [10].…”
Section: Science Is a Meta-puzzlementioning
confidence: 99%